1999
DOI: 10.1016/s0741-5214(99)70017-0
|View full text |Cite
|
Sign up to set email alerts
|

Midterm results of endovascular stented grafts for the treatment of isolated iliac artery aneurysms

Abstract: EGs appear to show satisfactory safety and efficacy for the repair of isolated aneurysms of the iliac arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 19 publications
2
36
0
2
Order By: Relevance
“…At this time, OR is the main treatment option of CIAAs that cause compressive symptoms because most IAAs do not decrease in size after EVAR. 39 Our review has the usual limitations of a large retrospective study. This is a single-center experience with CIAAs, including those who presented with associated AAAs.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…At this time, OR is the main treatment option of CIAAs that cause compressive symptoms because most IAAs do not decrease in size after EVAR. 39 Our review has the usual limitations of a large retrospective study. This is a single-center experience with CIAAs, including those who presented with associated AAAs.…”
Section: Discussionmentioning
confidence: 98%
“…Anastomotic endoleak occurred in 4% of the patients. 26 In a series of 28 isolated IAAs treated with EVAR, Parsons et al 39 reported four (12%) complications, that included embolization (n ϭ 1), wound dehiscence (n ϭ 2), and mucosal ischemia (n ϭ 1). One late rupture required conversion to OR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Our reintervention rate at 2 years was 14%, which compares favorably with other reports. 7,27,28 Given the difficulties in performing sonography in this region, however, this reintervention rate would suggest that these patients should get yearly CT follow-up until less rigorous follow-up, perhaps with duplex, can be proven safe.…”
Section: Discussionmentioning
confidence: 99%
“…3,4 However, EVR of bilateral SIAs may require occlusion of the internal iliac arteries, which can cause buttock claudication, colonic ischemia, and impotence in men. Both Melki et al 28 and Yano et al 29 reported buttock claudication or pelvic ischemia caused by intentional internal iliac artery occlusion in about 21% of patients.…”
Section: Discussionmentioning
confidence: 99%